PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - admin, FERDI NOVIANDI SAPUTRA B11112125 (Jurnal Manajemen Update, 2017)
Financial performance is one of the internal factors that affect the stock price of Go Public companies. The Study aim to reveal the effects of financial performance of companies on stock price of food and beverages companies listed in Indonesia Stock Exchange within 7 years (2009-2015). This research was conducted using secondary data. The samples in this research using purposive sampling method in order to obtain a sample of 15 companies during 7 years of the research. Data were analyzed using multiple linear regression analysis with SPSS 16.0 The results showed that the variables Current Ratio (CR), Return on Equity (ROE) and Earning Per Share (EPS) have positive effect and significant impact to the stock prices, variable Debt to Equity Ratio (DER) has positive effect but not significant to the stock price, and variable Inventory Turnover (ITO) has negative effect but not significant to the stock prices. Simultaneously variables Current Ratio (CR), Return on Equity (ROE), Earning Per Share (EPS), Debt to Equity Ratio (DER) and Inventory Turnover (ITO) affect the stock price in the food and beverages companies listed on the Indonesia Stock Exchange. Â  Keywords : Stock Price, Current Ratio, Debt to Equity Ratio, Return On Equity, Inventory Turnover, and Earning Per Share. Â